2022
DOI: 10.1007/s11869-021-01140-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of PM10-bound PAHs from non-exhaust sources

Abstract: Road traffic is a major source of airborne particles. While exhaust emissions have been deeply scrutinised, non-exhaust emissions deserved less attention despite their rising contribution to particle emissions from traffic. The mutagenicity of particulate matter (PM10) samples from wear between pavements and tyres and from road dust resuspension was determined by the Ames test with two Salmonella typhimurium strains (TA98 and TA100) with or without metabolic activation. After sequential extraction of PM10 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…TD also produced severe malformations in developing X. laevis embryos (Gualtieri et al, 2005a) First, it should be noted that studies on the inhalation toxicity of TRWP in mammalian models remain quite sparse. While some works do not find any harm induced by TRWP (Karlsson et al, 2008;Kreider et al, 2012;Lehner et al, 2020;Vicente et al, 2022), others clearly indicate a significant toxicological effect (Beretta et al, 2007;Gottipolu et al, 2008;Gualtieri et al, 2008Gualtieri et al, , 2005aGualtieri et al, , 2005bGustafsson et al, 2008;Karlsson et al, 2011Karlsson et al, , 2006Lindbom et al, 2007Lindbom et al, , 2006Liu et al, 2022;Mantecca et al, 2010Mantecca et al, , 2009aMantecca et al, , 2009bPoma et al, 2019). From the analysis of these papers, we can conclude that the TRWP effects may be mediated mainly by a pro-inflammatory response and oxidative stress, as described below.…”
Section: Analysis Of the Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…TD also produced severe malformations in developing X. laevis embryos (Gualtieri et al, 2005a) First, it should be noted that studies on the inhalation toxicity of TRWP in mammalian models remain quite sparse. While some works do not find any harm induced by TRWP (Karlsson et al, 2008;Kreider et al, 2012;Lehner et al, 2020;Vicente et al, 2022), others clearly indicate a significant toxicological effect (Beretta et al, 2007;Gottipolu et al, 2008;Gualtieri et al, 2008Gualtieri et al, , 2005aGualtieri et al, , 2005bGustafsson et al, 2008;Karlsson et al, 2011Karlsson et al, , 2006Lindbom et al, 2007Lindbom et al, , 2006Liu et al, 2022;Mantecca et al, 2010Mantecca et al, , 2009aMantecca et al, , 2009bPoma et al, 2019). From the analysis of these papers, we can conclude that the TRWP effects may be mediated mainly by a pro-inflammatory response and oxidative stress, as described below.…”
Section: Analysis Of the Resultsmentioning
confidence: 93%
“…The toxicity of TRWP has been associated mainly with the metallic constituents of non-exhaust PM but some studies have shown that these particles also contain polycyclic aromatic hydrocarbons (PAHs) (Vicente et al, 2022), many of which are potent mutagens and carcinogens. Therefore, metals (in particular Zn, Cd and Cu) and polycyclic aromatic hydrocarbons (PAHs) are key components driving the toxicity observed, which is consistent with the general literature on ambient PM.…”
Section: Mechanisms Of Toxicitymentioning
confidence: 99%